The Political Economy of Global Warming. From Data to Decisions - Erling Røed Larsen (Statistics Norway, Research Department, 2002)
This article studies the process from data acquisition to policy decision in relation to an optimum policy on global warming. Policymakers must be reasonably skeptical before proposing remedies to curb warming, but policymakers cannot await the final proof of any proposal's merit. Balancing evidence with doubt requires an informed approach, in which information is converted to knowledge and used to illuminate and compare human welfare connected to different scenarios. This article suggests, normatively, three essential elements for data based policies: evidence, consequence, and strategy. The presented framework for data based policymaking combines results from decision theory, economics, and political theory.
Keywords: C44; D78; H10; Q28; 330; data based; decision making; global warming; loss function; policymaking; social welfare; strategy; type-I error